Mapping the interdisciplinary terrain: a bibliometric analysis of islamic psychology and mental health research with implications for the study of destiny beliefs and marital infidelity - Hidayani Syam; Annisa 'Uliya Rasyida; Nofiardi Nofiardi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study addresses a critical gap in the literature on the intersection of destiny beliefs, marital infidelity, and Islamic theological perspectives, which remains largely unexplored in existing interdisciplinary research. Although studies on relationship beliefs, infidelity, and religiosity have grown significantly, the specific integration of psychological constructs of destiny beliefs with Islamic concepts of qadar and moral responsibility in the context of marital infidelity has not been systematically examined. To address this gap, the study employs a bibliometric analysis of Islamic psychology and related mental health literature as a proxy to map the broader intellectual landscape. Data were retrieved from the Scopus database (2023–2025) and analyzed using Biblioshiny (Bibliometrix R package), collaboration networks, and keyword co-occurrence patterns across 1,398 documents. The findings reveal that the literature is predominantly dominated by themes related to mental health, psychological well-being, religiosity, and survey-based methodologies. Importantly, the specific triadic relationship among destiny beliefs, marital infidelity, and Islamic theology appears only as a peripheral, weakly developed cluster within the broader network. This indicates that while supporting domains are expanding rapidly, the core conceptual integration remains underdeveloped and fragmented across disciplines. These results highlight an urgent need for more focused and integrative research that explicitly connects psychological theories of relationship beliefs with Islamic theological frameworks of destiny and moral accountability. Future studies should move beyond general religiosity and mental health themes to develop a coherent, interdisciplinary framework that better informs culturally and religiously grounded family counseling practices.